Outcomes After Severe Distal Tibia, Ankle, and/or Foot Trauma: Comparison of Limb Salvage Versus Transtibial Amputation (OUTLET). Issue 4 (April 2017) - Bosse, Michael J.; Teague, David; Reider, Lisa; Gary, Joshua L.; Morshed, Saam; Seymour, Rachel B.; Toledano, James; Cannada, Lisa K.; Steverson, Barbara; Scharfstein, Daniel O.; Luly, Jason; MacKenzie, Ellen J.
Abstract : Summary: Severe foot and ankle injuries are complex and challenging to treat, often requiring multiple operations to salvage the limb contributing to a prolonged healing period. There is some evidence to suggest that early amputation for some patients may result in better long-term outcomes than limb salvage. The challenge is to identify the regional injury burden for an individual that would suggest a better outcome with an amputation. The OUTLET study is a prospective, multicenter observational study comparing 18-month outcomes after limb salvage versus early amputation among patients aged 18–60 years with severe distal tibia, ankle, and foot injuries. This study aims to build upon the previous work of the Lower Extremity Assessment Project by identifying the injury and patient characteristics that help define a subgroup of salvage patients who will have better outcomes had they undergone a transtibial amputation. Abstract : Supplemental Digital Content is Available in the Text.